Inflammatory pseudotumor‐like follicular dendritic cell sarcoma of the spleen: A report of six cases with increased IgG4‐positive plasma cells. (28th May 2013) - Choe, Ji‐Young; Go, Heounjeong; Jeon, Yoon Kyung; Yun, Ji Yun; Kim, Young A; Kim, Hyun‐Jung; Huh, Jooryung; Lee, Hojung; Shin, Dong Hoon; Kim, Ji Eun
<x xml:space="preserve">Abstract</x> Inflammatory pseudotumor (IPT)‐like follicular dendritic cell (FDC) sarcoma is a rare neoplasm typically occurring in the spleen or liver. We present six cases of EBV+ IPT‐like FDC sarcoma of the spleen among Koreans along with their clinicopathologic features and IHC results. Most patients presented with an asymptomatic, incidentally detected single splenic mass and were successfully managed by splenectomy alone. Concomitant disease was found in one case, showing EBV+ gastric carcinoma with lymphoid‐rich stroma. Histologic features showed fibro‐inflammatory lesions that were often accompanied by necrosis and epithelioid histiocytic collection, which are barely distinguishable from IPT. Tumor cells did not frequently express conventional FDC markers, including CD21 (3/6 positive cases), clusterin (4/6), and D2‐40 (2/6), but showed uniform positivity for smooth muscle actin (SMA). Noticeably, significant numbers of IgG4+ plasma cells were found within all six tumors. We suggest that the diagnosis of IPT‐like FDC sarcoma should be made by the application of a panel of FDC markers, and CD21 negativity or SMA positivity cannot be the criterion for exclusion of IPT‐like FDC sarcoma. Relationship of IPT‐like FDC sarcoma of the spleen and IgG4‐related sclerosing disease should be investigated in further studies.